Dietary vegetable oils: Effects on the expression of immune-related genes in Senegalese sole (Solea senegalensis) intestine. Issue 1 (May 2015) - Montero, Daniel; Benitez-Dorta, Vanessa; Caballero, María José; Ponce, Marian; Torrecillas, Silvia; Izquierdo, Marisol; Zamorano, María Jesús; Manchado, Manuel
Abstract The decreased availability of fish oil, traditionally used as oil source in marine aquafeeds, has lead to the search for alternatives oils. Vegetable oils (VO) are being extensively used as lipid sources in marine fish diets, inducing an imbalance on certain dietary fatty acids. Alteration on the dietary ratio of w-6/w-3 has been described to have detrimental effects on fish immunity. Senegalese sole has high susceptibility to stress and diseases, and little is known on the effects of dietary VO on its immunity. In this study, Senegalese sole juveniles were fed diets (56% crude protein, 12% crude lipid) containing linseed (100LO), soybean (100SO) or fish (100FO) oils as unique oil source. Growth, cortisol and intestinal fatty acid composition were determined after 90 days. Moreover, at the final of the experiment a stress test (5 min of net chasing) was carried out. To evaluate the effect of diets and stress on intestine immunology, expression profiles of a set of 53 immune-related genes using RT-qPCR was also performed. The use of VO did not induced changes in fish growth, but affected fatty acid profile of intestine and expression of immune-related genes. The use of SO (rich in n-6 fatty acids) induced an over-expression of those genes related to complement pathway, recognizing pathogen associated to molecular patterns, defensive response against bacteria, defensive response against viruses, antigen differentiation, cytokines and their receptors. This general over-expression could indicate an activation of inflammatory processes in fish gut. When a stress was applied, a decrease of mRNA levels of different immune-related genes with respect to the unstressed control could be observed in fish fed 100FO. However, fish fed 100LO, with a higher ALA/LA ratio, seemed to ameliorate the effects of combined effects of FO substitution plus stressful situation whereas fish fed 100SO did not show this type of response.